2014
DOI: 10.5901/jesr.2014.v4n6p359
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Science Process Skills Teaching Approach on Secondary School Students’ Achievement in Chemistry in Nyando District, Kenya

Abstract: Science process skills are central to the acquisition of scientific knowledge which is useful in solving problems in society. In Kenya, students' achievement in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
1
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 26 publications
5
60
1
10
Order By: Relevance
“…The increasing of proportion items showed that the implementation of science process-oriented learning devices also greatly assist the students in understanding the theories or concepts being taught. The similar results was showed by Abungu [10] who states that science process skills can improve students' ability to understand a concept better than implementing other learning processes.…”
Section: A Mastery Of Learning Outcomessupporting
confidence: 80%
“…The increasing of proportion items showed that the implementation of science process-oriented learning devices also greatly assist the students in understanding the theories or concepts being taught. The similar results was showed by Abungu [10] who states that science process skills can improve students' ability to understand a concept better than implementing other learning processes.…”
Section: A Mastery Of Learning Outcomessupporting
confidence: 80%
“…This was consistent with studies from Ekon and Eni (2015) and Beaumont-Walters and Soyibo (2001) that indicated that gender did not significantly influence the acquisition of science process skills. However, a science process skills teaching strategy can make a significant difference in achievement in chemistry between boys and girls (Abungu et al, 2014). These findings were also consistent with the PISA 2012 results, in which it was reported that more than 50% of all countries in the project had no difference between science scores from genders.…”
supporting
confidence: 87%
“…Achievement of cognitive learning outcomes of students in this study can not be separated from the role of science process skills developed. This is because science process skills can help students gain an understanding of material that is more long term memory [12] . During the learning process, students do more of a series of science process skills independently to find facts, concepts or principles.…”
Section: Resultsmentioning
confidence: 99%